1979
DOI: 10.1002/ijc.2910230503
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cancer of the testis in young men

Abstract: An individual matched case-control study of testis cancer in 131 men under age 40 was conducted to investigate antecedent risk factors including events during prenatal life. Ten patients were born with an undescended testis compared to only two controls (p less equal to 0.02), a previously reported risk factor. Two new risk factors were uncovered: six patients-mothers received hormones during the index pregnancy compared to only one control-mother, and eight patient-mothers and two control-mothers reported exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
184
5
5

Year Published

1982
1982
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(212 citation statements)
references
References 12 publications
18
184
5
5
Order By: Relevance
“…However, the prevalence of cryptorchidism in patients with testicular cancer is only around 10% (United Kingdom Testicular Cancer Study Group, 1994;Schottenfeld, 1996) and therefore not likely in itself to account for the observed association between parity of the mother at birth and the risk of testicular cancer in the male offspring. Rather, our findings would be in line with the hypothesis that cryptorchidism and testicular cancer may be associated through shared risk factors (Henderson et al, 1979).…”
Section: Materials and Methods Cohortsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the prevalence of cryptorchidism in patients with testicular cancer is only around 10% (United Kingdom Testicular Cancer Study Group, 1994;Schottenfeld, 1996) and therefore not likely in itself to account for the observed association between parity of the mother at birth and the risk of testicular cancer in the male offspring. Rather, our findings would be in line with the hypothesis that cryptorchidism and testicular cancer may be associated through shared risk factors (Henderson et al, 1979).…”
Section: Materials and Methods Cohortsupporting
confidence: 88%
“…It has been hypothesized that high levels of endogenous oestrogens during critical stages of development in utero may increase the risk of cryptorchidism and testicular cancer (Henderson et al, 1979;, and at least three studies have found some evidence for increased oestrogen levels in first compared with later pregnancies (Bernstein et al, 1986;Panagiotopoulou et al, 1990;Key et al, 1996). Other studies also tend to support this hypothesis (McLachlan et al, 1975;Depue, 1984;Brown et al, 1986;Depue et al, 1983;Bernstein et al, 1988).…”
Section: Materials and Methods Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the odds ratio we found was higher, it was based on rather small numbers. In other studies in which it has been examined (Schottenfeld et al, 1980; Henderson et al, 1979) the relative risks obtained have not been statistically significant, although all four studies are consistent with an elevated risk of about 2-3-fold. There were too few (6) cases of infantile inguinal hernia to examine the relationship between side of hernia and side of tumour in those not having cryptorchidism.…”
Section: Resultsmentioning
confidence: 70%
“…Recent case-control studies (Schottenfeld et al, 1980;Henderson et al, 1979), of testicular cancer in young men, have found comparatively high rates of cryptorchidism in both cases and controls. This has led to the suggestion (Schottenfeld et al, 1980) that cryptorchidism is increasing.…”
Section: Resultsmentioning
confidence: 99%